Tribological Study Of A Bronze Obtained By Sintering Proceeds - Keraghel, F.; Loucif, K.; Delplanck, M. P. (University of Eloued جامعة الوادي, 2017)
Friction is a widely observed phenomenon requiring scientific capacity in the tribological behavior of materials. Reliability specialists use language borrowed from the doctors, so they talk about teething, durations of life and death, it is true that the machines as living beings, are born, wear, get tired, suffer defaults and eventually die; That is to say, are reformed, but the comparison stops, because the machines have no nervous system or bloodstream, do not think and feel no pain. Factors that may affect the life, or the factors that affect wear are very numerous: surface characteristics, operating conditions of the lubricant, the atmosphere, and finally the time. In this work we present the effect of speed and load on the tribological characteristics of a Cu 8% Sn bronze pressure sintered self-lubricating mode for two lubricants with different viscosities.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 01
Keywords: sintering; powder metallurgy; tribology; lubrication; copper alloy.